Understanding Contextual Aspects of the Word ‘Look’ in Corpus of Contemporary American English: Semantics Study - Hani Rahmah; Ervina CM Simatupang (Universitas Cokroaminoto Palopo, 2024)
This research investigates the contextual aspects and lexical semantics of the word